Pelatihan Berwirausaha Melalui Pengolahan dan Pemasaran Digital Produk Lokal Nias di SMK Negeri 1 Hiliduho - Laoli, Eka Septianti; Bate’e, Riston Iman; Gea, Erna Sepriani; Gea, Abdiel Aryanto; Hia, Aerani Calista Sintkhe; Daeli, Nurtitian; Gea, Kezia Irene; Lase, Silfiani Defar Sitine; Harita, Epifania Anggun Yunita; Hulu, Ardin (Indo-MathEdu Intellectuals Journal, 2026)
The low level of engagement of Vocational High School (SMK) students in local product processing and digital marketing demonstrates the need for more practical entrepreneurship learning. This Community Service (PKM) activity aims to improve students' skills in processing products made from cassava and bananas, typical of Nias, and strengthen their digital marketing capabilities. The activity was held at SMK Negeri 1 Hiliduho, involving 100 participants, consisting of teachers and students. The method used was practice-based training accompanied by mentoring in product processing, packaging, and digital marketing. The activity's success was evaluated through observations of participant engagement, product assessments, and interviews with teachers and students regarding the benefits of the training. Results showed that participants were able to independently produce locally sourced food products, apply more hygienic and attractive packaging techniques, and develop promotional content for social media and marketplaces. In addition to improving technical skills, this activity also encouraged students' entrepreneurial motivation and strengthened teachers' commitment to integrating locally sourced entrepreneurial practices into their learning. These findings indicate that practice-based training combined with digital marketing effectively strengthens entrepreneurial competencies while supporting the utilization of local food potential in the school environment.